Interactions Between Phytochemicals and Minerals in Terminalia ferdinandiana and Implications for Mineral Bioavailability - Akter, Saleha; Netzel, Michael; Tinggi, Ujang; Fletcher, Mary; Osborne, Simone; Sultanbawa, Yasmina (Frontiers in Nutrition, 2020)
Oxalic and phytic acid are phytochemicals considered to be anti-nutritional factors as they are predominantly found as oxalates and phytates bound to minerals like calcium and potassium. Studies have associated excessive oxalate consumption with increased urinary excretion of oxalate (hyperoxaluria) and calcium oxalate kidney stone formation, and excessive phytate consumption with decreased bioaccessibility and bioavailability of certain minerals and reduced utilisation of dietary protein. However, other studies suggest that dietary consumption of phytate may be beneficial and inhibit formation of calcium oxalate kidney stones. In light of these conflicting reports, dietary intake of oxalate and phytate enriched plants should be considered in relation to potential health outcomes following consumption. Terminalia ferdinandiana is one such plant and is investigated here with respect to oxalate, phytate, and mineral contents. Assessment of oxalate and phytate contents in T. ferdinandiana fruit, leaf, and seedcoat tissues through hydrolysis into acid forms revealed oxalic acid contents ranging from 327-1420 mg/100g DW whilst phytic acid contents ranged from 8.44-121.72 mg/100g DW. Calcium content in the different tissues ranged from 131-1343 mg/100g. There was no correlation between oxalic acid and calcium, however a significant, positive correlation was observed between phytic acid and calcium (r= 0.9917; p <0.001), indicating that tissues rich in phytic acid also contain higher levels of calcium. The high content of phytic acid in comparison to oxalic acid in T. ferdinandiana fruit found in this study and the dietary significance of this in terms of calcium bioavailability, needs to be investigated further.